Receptor complexes for each of the Class 3 Semaphorins - Harvey, Alan R. (Frontiers in Cellular Neuroscience, 2012)
The Class 3 Semaphorins (Sema3s) are a sub-family of proteins whose known biological roles are varied and growing. The mechanism of action of the Sema3s requires binding to transmembrane receptors that comprise heteromeric complexes of Neuropilins, Plexins and cell adhesion molecules (CAMs). However, knowledge of the receptor components of the Sema3s remains incomplete, and there may be receptor components which are yet undiscovered. The receptor complexes of the Sema3s share receptor components with each other, and it is the specific combination of these components within a heteromeric complex that is thought to give rise to selective binding and signalling for individual Sema3s. This crosstalk makes it experimentally difficult to define a single holoreceptor for each Sema3. Furthermore, the receptor composition for a given Sema3 may differ between cell types, and change as a function of developmental state or pathological situation. Nevertheless, there are at least some known differences in the constitutive structure of the receptors for the Sema3s. For example in neural cells, Sema3a and Sema3f signal through different Neuropilins (Nrp1 and Nrp2 respectively) and L1cam only appears important for Sema3a signaling, while Nrcam forms a complex with Nrp2. Further complexity arises from crosstalk of other families of ligands (e.g. VEGF) with Sema3 receptor components. Thus the Sema3s, which have been shown as antagonists for each other, can also act as antagonists for other families of molecules. This review compiles experimental evidence describing the receptor components for the Sema3s, detailing the current state of knowledge of which components are important for signaling of each Sema3 before going on to consider possible future directions for the field.